Effect of pre-operative expectations on the outcomes following total shoulder arthroplasty. (September 2017) - Swarup, I.; Henn, C. M.; Nguyen, J. T.; Dines, D. M.; Craig, E. V.; Warren, R. F.; Gulotta, L. V.; Henn III, R. F.
Abstract : Aims: Few studies have evaluated the relationship between patients' pre-operative expectations and the outcome of orthopaedic procedures. Our aim was to determine the effect of expectations on the outcome after primary anatomical total shoulder arthroplasty (TSA). We hypothesised that patients with greater expectations would have better outcomes. Patients and Methods: Patients undergoing primary anatomical TSA completed the Hospital for Special Surgery's Shoulder Expectations Survey pre-operatively. The American Shoulder and Elbow Surgeons (ASES), Shoulder Activity Scale (SAS), Short-Form-36 (SF-36), and visual analogue scale (VAS) for pain, fatigue, and general health scores were also collected pre-operatively and two years post-operatively. Pearson correlations were used to assess the relationship between the number of expectations and the outcomes. Differences in outcomes between those with higher and lower levels of expectations for each expectation were assessed by independent samples t -test. Multivariable linear regression analysis was used to control for potential confounding factors. Results: A total of 67 patients were evaluated two years post-operatively. Most parameters of outcome improved significantly from baseline and most patients were satisfied. A greater number of expectations was associated with a significantly greater improvement in the ASES score (p = 0.02). In the multivariable analysis, a greater number of expectations was an independent predictor of better ASES, VAS and SF-36 scores, as well as improvements in ASES and VAS pain scores (p < 0.05). Greater expectations for many specific expectation questions were significantly associated with better outcomes (p < 0.05). Conclusion: TSA is a successful procedure with significant improvements in outcome, and greater pre-operative expectations are associated with better outcomes. Cite this article: Bone Joint J 2017;99-B:1190–6.